New method to extract the model parameters of solar cells from the explicit analytic solutions of their illuminated I–V characteristics - Ortiz-Conde, Adelmo; García Sánchez, Francisco J.; Muci, Juan (Solar energy materials and solar cells, 2006)
We present a new method to extract the intrinsic and extrinsic model parameters of illuminated solar cells containing parasitic series resistance and shunt conductance. The method is based on calculating the Co-content function (CC) from the exact explicit analytical solutions of the illuminated current–voltage ( I–V) characteristics. The resulting CC is expressed as a purely algebraic function of current and voltage from whose coefficients the intrinsic and extrinsic model parameters are then readily determined by bidimensional fitting. The procedure is illustrated by applying it to experimental and synthetic I–V characteristics and an analysis of the errors is presented.